Identification of formation mechanism and key elements of quality geriatric care behavior of nursing assistants in nursing homes: a grounded theory study - Liao, Lulu; Bai, Xue; He, Xiaoxiao; Tan, Lei; Yang, Linghua; Long, Huan; Huang, Shenglan; Li, Xia; Han, Ying; Peng, Xiao; Chen, Huijing; Yang, Xiufen; et al. (Frontiers in Public Health, 2024)
Objective(s) This study aimed to identify the key elements and develop a formation mechanism model of quality geriatric care behavior for nursing assistants. Methods This qualitative research employed the strategy of grounded theory proposed by Strauss and Corbin. Furthermore, the data was collected by participatory observation and semi-structured interviews. A total of 12 nursing managers, 63 nursing assistants, and 36 older people from 9 nursing homes in 6 cities were interviewed, whereas for the observatory survey, participants were recruited from 2 nursing homes. Results The comparative and analysis process revealed 5 key elements of quality geriatric care behavior, including holistic care, personalized care, respect, positive interaction, and empowerment. Based on the Capability-Opportunity-Motivation-Behavior (COM-B) model, key elements and the 3 stages of quality geriatric care behavior (negative behavior cognition stage, practice exchange run-in stage, and positive behavior reinforcement stage), the theoretical framework of the formation mechanism was established. Conclusion The results indicated that nursing assistants’ capabilities, motivation, and organizational and environmental support are vital for quality care behaviors. The theoretical framework established in this study provides theoretical support and practical reference to policymakers, institutional administrators, and healthcare professionals for improving nursing assistant’s care behaviors.